An improved limit for Γee of X(3872) and Γee measurement of ψ(3686) - M. Ablikim; M.N. Achasov; X.C. Ai; O. Albayrak; M. Albrecht; D.J. Ambrose; A. Amoroso; F.F. An; Q. An; J.Z. Bai; R. Baldini Ferroli; Y. Ban; et al. (Physics Letters B, 2015)
Using the data sets taken at center-of-mass energies above 4 GeV by the BESIII detector at the BEPCII storage ring, we search for the reaction e+e−→γISRX(3872)→γISRπ+π−J/ψ via the Initial State Radiation technique. The production of a resonance with quantum numbers JPC=1++ such as the X(3872) via single photon e+e− annihilation is forbidden, but is allowed by a next-to-leading order box diagram. We do not observe a significant signal of X(3872), and therefore give an upper limit for the electronic width times the branching fraction ΓeeX(3872)B(X(3872)→π+π−J/ψ)<0.13 eV at the 90% confidence level. This measurement improves upon existing limits by a factor of 46. Using the same final state, we also measure the electronic width of the ψ(3686) to be Γeeψ(3686)=2213±18stat±99sys eV.